Experimental Investigation of Aerodynamic Characteristics of Dimpled 3D Aircraft Wing - V L Jagannatha Guptha; Ramesh S Sharma; D Harish (International Journal of Mechanical Dynamics and Systems Analysis, 2023)
There is a strong demand for innovative designs, optimization of the aircraft components for their parts with respect to design, etc. One such innovation is by introduction of dimples in the wing of the aircraft. To study the effect of geometry modification of the wing, the present work compares the aerodynamic efficiency, ratio of lift to drag coefficients, along with different aerodynamic characteristics of an Inward and outward circular dimpled aircraft wing with an un-dimpled wing by using 3D structures for NACA 2412 airfoil. A diameter of 300mm for dimples, with 8 and 16 numbers of circular dimples, both inward and outward type, at 0o to 16o angle of attack with range of 4o interval was considered. 3D aircraft wing models were simulated in CATIA V5 software tool and fabricated by 3D Printing method. The wind tunnel test results show that the Inward circular dimpled aircraft wing model with 16 numbers of dimples has the highest aircraft efficiency of 10.69. Thus 16 dimples were selected and analyzed for various angles of attack from 0o to 16o. Lift force is maximum for an inward 16 circular dimpled aircraft wing of 5.74 N followed by 4.57 N for un-dimpled aircraft wing and 4.38 N for outward 16 circular dimpled aircraft wing, at 16o Angle of attack. The lower drag force of 0.73 N is for an outward 16 circular dimpled aircraft wing compared to both un-dimpled and inward 16 circular dimpled aircraft wings, at 16o angle of attack.
Keywords: 3D printing; Aerodynamic efficiency; Aircraft wing; CATIA V5; Dimpled wing